Pengaruh Reward Dan Punishment Terhadap Profesionalisme Guru - Mirzon Daheri; Petrus Jacob Pattiasina; Nanda Saputra; Nana Meily Nurdiansyah; Lailatul Uzlifah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study aims to test the validity and practicality of teaching materials E-module Dilan Android-based (Didroid) on hot material for elementary school students. The research method applied is Research and Development (R&D) method with Sugiyono development model. This study uses data collection techniques in the form of observation, interviews and questionnaire instruments filled by media experts, material experts, as well as student and teacher users. Data analysis techniques used are quantitative and qualitative analysis to describe the results of the questionnaire assessment. The results showed that the E-module Didroid developed meet the criteria of valid and practical. The results of media validation get a score of 100 so that it is included in the very valid category. The results of the validation of the material get a score of 96.7% on the aspect of Self Instruction, a score of 100% on the aspect of Self Contained, a score of 80% on the aspect of Self Alone, a score of 93.3% on the aspect of self adaptive, and a score of 80% on the aspect of User Friendly so that it enters the category of very valid and valid. The results of the practicality of student users get a score of 90% and teacher users get a score of 100% so that it enters the category of very practical. It can be concluded that the E-module developed Didroid valid, practical, and feasible to use in science learning in Grade V Elementary School. E-module Didroid easy to understand, easy to use, attractive, and can be used as a reference teaching materials that use digital technology.